Pelatihan Pertolongan Pertama Gawat Darurat (PPGD) untuk Orang Awam di SMA Negeri 14 Maros Sulawesi Selatan - Alfyan Rahim; Sri Wahyuni; Wahyuni Wahyuni; Siti Rahmani; Sri Rahma Haruna (Universitas Mathla'ul Anwar Banten, 2021)
EMERGENCY FIRST AID TRAINING FOR LAY PEOPLE AT SMA 14 MAROS, SOUTH SULAWESI. First aid for accidents is an important aspect of everyday life, be it at home, on the road, at school, or at the office, because emergency events need to be handled immediately at the scene. The principle of HELP is considered necessary for all levels of society, because it can help people or victims to receive professional medical care. First Aid can be done by either the general public or students, until professional medical help arrives to treat the victim. The methods used in this activity are lectures, question and answer discussions, and direct practice using phantoms as victims. Before carrying out the core activities, questionnaires were distributed for the pre-test and it was found that the community service participants were still in the low level of knowledge category. The conclusion is that there was a change in the level of knowledge before and after this training activity, and the enthusiasm of the participants was very high in practicing first aid for accident victims.